Match or Mismatch of Expectation-Realization Behind the Motives in Supporting Social Entrepreneurship Programs - Prama Widayat; Afred Suci; Sri Maryanti; Lucky Lhaura Van FC; Abu Amar Fauzi; Satria Tri Nanda (Universitas Hayam Wuruk Perbanas, 2023)
Abundant studies regarding motives in social enterprise have been conducted but have barely explored the gaps between motivational expectations and realizations. Particularly in waste bank studies, such a study has yet to be scholarly discussed. Using expectancy theory and mismatch hypotheses, this study explored the motives in waste bank participation towards owners/managers and customers and measured the gaps between the motive expectations and realizations. Quantitative comparison tests were employed on 45 Indonesian waste bank owners/managers and 162 customers whose data were collected directly and through online surveys. The findings reveal that the most expected motive was the environmental, while the least was the economic; this went for both waste bank owners/managers and customers. The results also show that severe mismatches occurred between expectations and realizations, in which the most significant gap for waste bank owners/managers was educational, while the environmental motive was the biggest for customers. This study's findings enrich the social entrepreneurship literature by showing that the motives per se are insufficient to reveal individuals' actual situations in supporting the social programs, as disparities are very likely to occur between expectations and realities. The gap analysis in this study provides a different alternative to conducting studies related to the underlying motives for supporting social entrepreneurship programs.